A controller for practical stability of capacitor voltages in a five-level diode-clamped converter. (March 2016) - Umbría, Francisco; Gordillo, Francisco; Salas, Francisco
Abstract: The balancing of the dc-link capacitor voltages represents the main technical challenge in multilevel diode-clamped converters. In particular, when the number of capacitors is greater than two, these power conversion systems must be actively controlled to achieve a correct voltage sharing. Focusing on the five-level diode-clamped converter topology, this paper deals with the voltage imbalance phenomenon from a control point of view. For that purpose, the voltage balancing objective is addressed as a problem of ensuring the practical stability of a nonlinear system under the presence of external disturbances. Considering this approach, a novel control method is proposed to regulate the outputs of the system. It is based on several steps, which should be carried out during the controller design stage, that lead to define a discrete-time controller with sampling frequency corresponding to the triple of the ac-source frequency. Finally, the performance of the proposed controller is analyzed under varying operating conditions to demonstrate the capability and viability of the controller to attain the control goals.